Administration of a mixture of triterpenoids from yeyachun and phenolic acids from danshen ameliorates carbon tetrachloride-induced liver fibrosis in mice by the regulation of intestinal flora - Yang Tan; Yuyan Li; Feng Zhou; Jinming Guo; Tao Wang; Yuhe Shi; Yantao Yang; Jiandong Lu; Gang Pei (Elsevier, 2020)
yeyachun and danshen exist as Chinese patent medicine, Xuemai Tong, and are clearly effective at alleviating liver fibrosis (LF). Previous studies have indicated that triterpenoids from yeyachun (EFT), and phenolic acids from danshen (SMP) are effective in the treatment of LF. The regulation of intestinal flora is an effective method for treating LF. The aim of this study was to investigate the effect of a mixture of EFT and SMP on carbon tetrachloride (CCl4) induced LF. Our results showed the mixture significantly decreased liver damage and fibrosis index, and maintained liver tissue composition, compared to the model group. Moreover, the imbalance of symptoms of intestinal flora was improved. The mixture also caused changes to metabolites of gut flora. Furthermore, the expression of CD68 in liver tissues from the treated groups was significantly decreased when compared to the model group. However, no significant difference was observed from microstructure of gut tissues and LPS concentrations in the serum between mixture treated mice and model mice. This study suggests that the mixture of EFT and SMP had a significant effect on CCl4 induced LF, and the mechanism of this action, at least in part, involved the regulation of intestinal flora and their metabolites.